EFL Student’s Perceptions on The Use of Instagram in Supporting Speaking Practice - Widari, Kadek Indah (Jurnal Ilmu Multidisiplin Indonesia, 2024)
This research investigates students' perceptions of using Instagram, particularly its reels feature, to support English- speaking practice in Class XI at SMK TI Bali Global Singaraja. With the growing popularity of social media among teenagers, this study aims to explore the potential of incorporating Instagram as an innovative and engaging learning tool to enhance students' English-speaking skills. A qualitative approach was employed, utilizing questionnaires and semi-structured interviews as the main data collection instruments. The study involved 20 purposively selected Class XI students. The findings reveal that most students hold a positive view of using Instagram reels to support speaking practice. They value the accessibility, convenience, and engaging content provided by Instagram Reels. Students perceive Reels as a valuable supplementary learning resource that strengthens language concepts, improves pronunciation, expands vocabulary, and builds confidence in speaking English. This study offers valuable insights for educators and practitioners on exploring social media as an innovative and contextual medium to support English language teaching.